Lipid profile in children with insulin dependent diabetes mellitus - Dias, Bina; Maharana, Subhashini (International Journal of Research in Medical Sciences, 2017)
Background: Dyslipidemia is a significant risk factor for coronary heart disease which may lead to an increased risk of atherosclerosis in Type I diabetes mellitus at a younger age. Methods: Twenty five children with diabetes mellitus type 1 were assessed for the levels of glucose, total cholesterol, triglycerides, HDL, VLDL, LDL and cholesterol to HDL ratio and were compared with age; matched healthy controls. Results: The result of the present study showed that all the above mentioned parameters were significantly (P<0.001) higher in type 1 diabetes mellitus as compared to the control group with glucose levels of 217.5 mg/dl, triglycerides levels of 156.5 mg/dl, cholesterol levels of 184.7 mg/dl, VLDL levels of 31.08 mg/dl, LDL levels of 120.1 mg/dl and cholesterol to HDL ratio of 5.87 whereas HDL levels were significantly lower i.e. 32.7 mg/dl in type 1 diabetes mellitus. Conclusions: The patients are at a higher risk of developing atherosclerosis and dyslipidemia at an early age.